2010
DOI: 10.5194/acp-10-6151-2010
|View full text |Cite
|
Sign up to set email alerts
|

Regional-scale geostatistical inverse modeling of North American CO<sub>2</sub> fluxes: a synthetic data study

Abstract: Abstract.A series of synthetic data experiments is performed to investigate the ability of a regional atmospheric inversion to estimate grid-scale CO 2 fluxes during the growing season over North America. The inversions are performed within a geostatistical framework without the use of any prior flux estimates or auxiliary variables, in order to focus on the atmospheric constraint provided by the nine towers collecting continuous, calibrated CO 2 measurements in 2004. Using synthetic measurements and their ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
155
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(160 citation statements)
references
References 37 publications
5
155
0
Order By: Relevance
“…Geostatistical approaches have been applied to many fields in the Earth and environmental sciences, including geology, ecology, and hydrology to study spatial phenomena (e.g., Chiles and Delfiner, 1999;Webster and Oliver, 2007). In studying land-atmosphere carbon dynamics, geostatistical inversion modeling has been used to estimate the spatial distribution of carbon sources and sinks both globally, and regionally over North America (e.g., Michalak et al, 2004;Gourdji et al, , 2010Mueller et al, 2008). Geostatistical regression approaches, such as the one described here, have been used regionally to evaluate the relationship between environmental variables (e.g., Erickson et al, 2005), and have recently been applied to evaluate the potential controls on carbon uptake and release at flux tower sites in North America (NA) (e.g., Mueller et al, 2010;Yadav et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Geostatistical approaches have been applied to many fields in the Earth and environmental sciences, including geology, ecology, and hydrology to study spatial phenomena (e.g., Chiles and Delfiner, 1999;Webster and Oliver, 2007). In studying land-atmosphere carbon dynamics, geostatistical inversion modeling has been used to estimate the spatial distribution of carbon sources and sinks both globally, and regionally over North America (e.g., Michalak et al, 2004;Gourdji et al, , 2010Mueller et al, 2008). Geostatistical regression approaches, such as the one described here, have been used regionally to evaluate the relationship between environmental variables (e.g., Erickson et al, 2005), and have recently been applied to evaluate the potential controls on carbon uptake and release at flux tower sites in North America (NA) (e.g., Mueller et al, 2010;Yadav et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The model has been used extensively in regional simulations and inversion studies for different greenhouse gases (Lin et al, 2003(Lin et al, , 2004Gerbig et al, 2003b;Miller et al, 2008;Gourdji et al, 2010;Göckede et al, 2010). A brief description of STILT is given as follows.…”
Section: Wrf/stilt-vprm Modelmentioning
confidence: 99%
“…Several studies have reported the advantages of using coupled Eulerian-Lagrangian models, and some have used the WRF-STILT modelling system (Nehrkorn et al, 2010) to estimate the CO 2 surface fluxes over North America (Gourdji et al, 2010). Rigby et al (2011) and Koyama et al (2009) outlined a method for combining information on the emissions-mole fraction sensitivity from Eulerian and Lagrangian chemical transport models, for use in estimating emissions at a global scale.…”
Section: Introductionmentioning
confidence: 99%